BAHASA BALI DIALEK BULELENG DAN MENTALITAS ORANG BULELENG; TINJAUAN DARI PERSPEKTIF FILSAFAT BAHASA - Komang Puteri Yadnya Diari; I Ketut Suara Antara (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2023)
The Buleleng people are famous for the Balinese language known as the Bulelengan base, the Buleleng people are widely known as unique and different people compared to other Balinese people. The special difference lies in that they use a special accent called the Bulelengan language. The Balinese language of Buleleng is often considered "weird" by the people of southern Bali in particular, so the language used is often considered "rough" by some people. Whereas the Buleleng dialect of Balinese actually shows an egalitarian attitude and does not look at status, which reflects the character and mentality of the Buleleng people. The Balinese dialect of Buleleng is essentially a way for the Buleleng people to show their existence as stated by Hans-Georg Gadamer that language is not just a sign system, not a form, and not only a means, but ontologically, language is an appearance of "being" in humans. Therefore, language is captured by humans not only as a mere empirical reality but rather as an ontological reality.